OSTEOPOROSIS AND PROBIOTICS - Santos, Thaís Aguiar [UNESP]; Ribeiro, Jaqueline Lemes [UNESP]; Anbinder, Ana Lia [UNESP] (My University, 2021)
Osteoporosis; a systemic, chronic, and multifactorial disease characterized by low bone mass and bone tissue microarchitectural degradation; is considered an important public health problem worldwide. One of the most common causes of osteoporosis is post-menopausal hormonal deficiency, which leads to an imbalance in the bone remodeling process, and increased bone loss and fracture risk. The current treatments for osteoporosis, however, are not risk-free. This has led to the study and development of new possibilities for osteoporosis treatment, including the use of probiotics. Probiotics are live, non-pathogenic microorganisms that confer health benefits to the host when administered in adequate amounts. The promising use of probiotics relies on the possibility of preventing and treating bone loss with a natural, safe, and non-invasive method, besides the good results obtained in vivo and in patients. The most commonly used genus in osteoporosis studies is Lactobacillus, although the possible mechanisms of action are diverse. The latest research has demonstrated a strong correlation between the intestinal microbiota and bone metabolism, involving the interaction between the immune system and bone cells, as well as the regulation of the intestinal epithelial barrier function through tight junction proteins. As the intestinal microbiota has become a new target for studies to improve bone health, and in view of the growing use of probiotics, this chapter reviews the literature in order to improve the understanding of the mechanisms of action, and to discuss the effectiveness of probiotics in the treatment and prevention of osteoporosis.